Investigating a key autophagy protein-protein interaction and its modulation by phosphorylation and an ALS-related mutation - Brennan, Andrew (2019)
Autophagy is a cellular degradation pathway which removes cytoplasmic material including protein aggregates, damaged organelles and pathogens. The interaction of the autophagy adaptor p62 with lipid-anchored hAtg8 receptor proteins is a key step in this process whereby cargo bound to p62 is sequestered to the autophagosomal membrane. Here it is engulfed for transport to the lysosome where it is enzymatically degraded. Recruitment of p62 filaments to the autophagosome membrane also plays an important role in autophagosome expansion. The p62-hAtg8 interaction is mediated by the Atg8-interacting motif (AIM) which is a short sequence present in many autophagy adapter/receptor proteins.